Catalytic stereoselective semihydrogenation of alkynes to E-alkenes. - Michaelides, I; Dixon, D (2013)
Less is more: Significant advancements have been made in recent years in the development of the E-selective, catalytic, functional-group-tolerant semihydrogenation of alkynes to E-alkenes through transition-metal catalysis (see scheme). For this type of catalysis, the use of mononuclear metal catalysts is superior to that of multinuclear metal catalysts. Copyright © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.